1978
DOI: 10.1007/bf00154928
|View full text |Cite
|
Sign up to set email alerts
|

Properties of the solar chromosphere H? spicules as observed spectrally

Abstract: Time succession of 25 Ha spicules has been studied. The spectra are obtained at a height of 6 arc sec during 21 rain (38 pictures) with the 53 cm Lyot coronagraph. Total intensities W, widths AA and radial velocities Vr are determined (about 650 Ha line profiles). For 14 spicules the sign of V, varies, for the rest the sign variation is absent or it is doubtful. Characterized period of Vr variation is 3-7 rain with a mean amplitude of • km s -1. W and AA also vary with a similar period and mean amplitudes equa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0
1

Year Published

1980
1980
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 5 publications
3
11
0
1
Order By: Relevance
“…A4, page 6 of 7 b) Our work presented here and other studies using both filtergrams and limb spectra (Pasachoff et al 1968;Nikolsky & Platova 1971;Tanaka 1974;Kulidzanishvili & Nikolsky 1978;Gadzhiev & Nikolsky 1982;Suematsu et al 1995;Dara et al 1998;Georgakilas et al 1999 andrecently in Tavabi et al 2011a) clearly suggest that spicules are multicomponent. At each moment, we usually can only see just a part of it clearly; accordingly, the spatial and the temporal resolution should be better than the values of the diameter of each component and its lifetime.…”
Section: Discussionsupporting
confidence: 64%
“…A4, page 6 of 7 b) Our work presented here and other studies using both filtergrams and limb spectra (Pasachoff et al 1968;Nikolsky & Platova 1971;Tanaka 1974;Kulidzanishvili & Nikolsky 1978;Gadzhiev & Nikolsky 1982;Suematsu et al 1995;Dara et al 1998;Georgakilas et al 1999 andrecently in Tavabi et al 2011a) clearly suggest that spicules are multicomponent. At each moment, we usually can only see just a part of it clearly; accordingly, the spatial and the temporal resolution should be better than the values of the diameter of each component and its lifetime.…”
Section: Discussionsupporting
confidence: 64%
“…Indeed, the oscillations of Doppler velocity in spicules with similar periods were reported by Zaqarashvili et al (2007). If the velocity of the kink wave is polarized in the plane of observation, then it results in the Doppler shift of the observed spectral line (Nikolsky and Sazanov (1967);Pasachoff et al (1968); Kulidzanishvili and Nikolsky (1978); Gadzhiev and Nikolsky (1982); Kulidzanishvili and Zhugzhda (1983); Hasan and Keil (1984); Papushev and Salakhutdinov (1994); ; Kukhianidze et al (2006); Zaqarashvili et al (2007)). However, if the velocity is polarized in the perpendicular plane then it results the visible displacement of spicule axis along the limb (Nikolsky and Sazanov (1967); Nikolsky and Platova (1971); Gadzhiev and Nikolsky (1982); Papushev and Salakhutdinov (1994)).…”
Section: Mhd Kink Wavesmentioning
confidence: 58%
“…Oscillations are more frequently observed in the Doppler velocity, which points towards transversal motions as the observations are performed at the solar limb. The longitudinal velocity component may also take a part in shaping the Doppler velocity oscillations as spicules are Weart (1970) random random Hα Nikolsky and Platova (1971) 50-70 s Hα Kulidzanishvili and Nikolsky (1978) 3-7 min 3-7 min Hα Gadzhiev and Nikolsky (1982) 3-6 min 3-6 min Hα Kulidzanishvili and Zhugzhda (1983) 5-min 5-min Hα Hasan and Keil (1984) 2-3 min > 300 km/s Hα Papushev and Salakhutdinov (1994) 80-120 s 80-120 80-120 > 300 km/s Hα 5-min 5-min EUV Kukhianidze et al (2006) 35-70 s ∼ 80 km/s Hα Zaqarashvili et al (2007) 30-110 s ∼ 110 km/s Hα De Pontieu et al (2007a) 100-500 s 50-200 km/s Ca II generally tilted away from the vertical. However, the transverse component seems to be the more important and determinant component in these oscillations as the visible displacement along the limb is also frequently reported.…”
Section: Summary Of Observed Oscillatory Phenomenamentioning
confidence: 99%
“…The existence of 3-5 min oscillations in spicules were reported since a long time, for example by Kulidzanishvili and Nikolsky (1978). More recently similar periodic Under is shown a typical Y-t diagram (time-slice diagram) deduced from the analysis of a time sequence of similar images; it gives a ballistic-type motion (see also Suematsu et al, 1995), for the typical spicule shown by a linear mark on the top image, to the left.…”
Section: Introductionmentioning
confidence: 93%